Non Tuberculous Mycobacterium Infection with Cavernolith: A Rare Case Report - Anjana Ledwani; Babaji Ghewade; Vivek Alone; Ashwin Karnan (Journal of Clinical and Diagnostic Research)
Cavernolithiasis is defined as a calcified focus found inside a lung cavity. The patient can remain asymptomatic or exhibit non specific symptoms such as haemoptysis and recurrent chest infections. Its diagnosis poses a challenge to clinicians worldwide, making it a topic of interest. A collection of more than 190 various mycobacteria that cause infections in different body organs, especially the lungs, is collectively referred to as Non Tuberculous Mycobacteria (NTM). Hereby, authors report a rare case of cavernolithiasis in a 35-year-old-female patient with an NTM infection who was previously diagnosed and treated for Pulmonary Tuberculosis (PTB). This patient’s sputum was positive for Acid-fast Bacilli (AFB), and sputum culture showed growth of NTM species. High-resolution Computed Tomography (CT) of the thorax revealed bilateral cavitary lesions with the presence of calcified material inside the cavities. She did not require any surgical intervention and was managed conservatively. NTM infection poses a diagnostic challenge, making treatment milestones very difficult due to the complex treatment regimen involving multiple drugs administered for a prolonged period. Therefore, appropriate measures such as cessation of substance abuse, pulmonary hygiene, a nutritional diet, adherence to treatment, and regular follow-up must be taken to improve the quality of life.